DETERMINASI KONFUSIANISME DALAM ANALISIS WACANA KRITIS NOVEL KLASIK “JOURNEY TO THE WEST” - Melinda Rahmawati; Yustiara Nuraini; Bimo Rafi Widianto; Debi Robi Yanti; Sulaeman Sulaeman (Haluan Sastra Budaya, 2021)
The purpose of research to see the determination formed by Confucianism in critical discourse analysis of the classic novel "Journey To The West". The method used is descriptive qualitative with critical discourse analysis in historical approach (discourse-historical-approach). The result of this research is the presence of a Confucian determination based on the results of critical discourse analysis of discourse-historical-approach to the classic novel "Journey To The West" which is inherent as culture. The conclusion of this research is that there are Confucian values depicted in the classic novel "Journey To The West" through the characterization of the characters in the novel so that Confucianism remains inherent in Chinese society.